Voting based extreme learning machine - Cao, Jiuwen (2013)
This paper proposes an improved learning algorithm for classification which is referred to as voting based extreme learning machine. The proposed method incorporates the voting method into the popular extreme learning machine (ELM) in classification applications. Simulations on many real world classification datasets have demonstrated that this algorithm generally outperforms the original ELM algorithm as well as several recent classification algorithms.